Penggunaan Media Video Berbasis Capcut dalam Pembelajaran Mengidentifikasi Unsur Teks Berita pada Siswa Kelas VIII MTs Negeri 1 Kabupaten Gorontalo - Fitri Lamusu; Salam Salam; Herson Kadir (Ideas Publishing, 2023)
The purpose of this study was to describe the use of Capcut-based video media in learning to identify the elements of news text on students, student learning outcomes, and inhibiting factors in the use of Capcut-based video media. This research uses descriptive method with qualitative research type. Based on the results of the study, it is stated that the use of Capcut-based video media in learning to identify the elements of news text has been successfully used so that student learning outcomes reach competency standards, and in accordance with RPP. The assessment of identifying the elements of news text on students in the knowledge aspect is in the form of text described in the student worksheet.